Reformasi Agraria dan Dampaknya terhadap Perekonomian Indonesia pada Era Orde Lama dan Orde Baru - Lubis, Mira Ardilla; Abdilla, Muhammad Fajar; Berutu, Siti Sardiana (Analisis Sejarah, 2024)
Agrarian reform encompasses a series of government actions and policies designed to restructure the land system, aiming to enhance social justice, reduce land ownership inequality, increase agricultural productivity, and stimulate economic growth in the agricultural sector. These reforms typically involve transferring land from large owners to smaller farmers, improving the land ownership structure, and granting land to farmers. This study employs descriptive qualitative research. According to Lexi J. Moleong, qualitative research seeks to understand phenomena experienced by the subjects. Although agrarian reform in Indonesia began during Dutch colonialism, significant reforms were implemented during the Old Order and New Order eras, particularly through Law Number 5 of 1960, known as the Basic Agrarian Law (UUPA). This law established regulations related to agrarian principles during the Old Order period. The Old Order’s agrarian reform aimed to dismantle colonial capitalism and feudalism by nationalizing foreign companies and redistributing land. However, agrarian reform in Indonesia still faces numerous challenges that need to be addressed to ensure inclusive and sustainable economic growth.